Análise regional de funções hidrológicas aplicáveis à avaliação de vazões mínimas nas bacias hidrográficas dos rios Itapemirim e Itabapoana (ES) - Silva Júnior, Carlos Alberto da (2014)
Flood estimation is seen as an alternative to obtain indirect hydrological information, since it allows the transference of information from one location to another within an area with similar hydrological behavior. The transference of information usually occurs by means of a mathematical function in which the regionalized hydrological variable is dependent on climatological and geographical variables of the basin in study. The study's objective was to establish regional functions to define flow duration curves and low flow frequency curves to water courses of the Itapemirim and Itabapoana River basin, important water systems of the southern portion of the Espirito Santo state, Brazil. In order to obtain regional functions, methods of characteristic values, exponential curve and dimensionless curve method were employed. Drainage area, total length of water courses, length of main river, basin perimeter, average slope of water courses, and average rainfall of long duration were considered the independent variables in the regionalization process. Regional functions obtained from such methods of regionalization reproduced satisfactorily the flow permanence curves. However, the established regional functions did not allow proper conformation of the low flow frequency curves.